Guest

If a square*sec square theta - b square tan square theta= c square; prove that; sin theta=+- √c square - a square/ c square-b square

If a square*sec square theta - b square tan square theta= c square; prove that; sin theta=+- √c square - a square/ c square-b square

Grade:10

1 Answers

Arun
25757 Points
5 years ago
Dear Ankita
a2 secc2 x –b2 tan2 x = c2
now
a2 + a2 tan2x – b2 tan2x = c2
tan2 x = (c2 – a2)/ (a2 – b2)
tan x =√(c2 – a2)/ (a2 – b2)
now you can solve all the trigonometric ratio.
Regards
Arun (askIITians forum expert)

Think You Can Provide A Better Answer ?